Multi-regional input-output tables for macroeconomic simulations in Poland's regions - Ageliki Anagnostou; Paweł Gajewski (Economies, 2021)
The capacity of multi-regional input-output tables (MRIOTs) to investigate linkages across structures and subnational regions within a country makes them a useful and solid tool of various types of simulations. This study develops MRIOTs for the Polish regions that can be subsequently employed to macroeconomic simulations, including assessing internal policy impulse responses or testing the regional economic resilience to external shocks. For this purpose, we build three macro-regions, discuss how their structural features validate their use to study differentials in economic policy effects or regional economic resilience, and finally, describe the process of constructing the MRIOTs.
Keywords: 330; CGE; CHARM method; multi-regional I-O tables